Building Capacity of Community Sport Clubs to Increase Female Participation. (19th September 2022) - Hanlon, Clare; Millar, Patti; Doherty, Alison; Craike, Melinda
Abstract: Despite the benefits of participating in the physically active leisure pursuit of sport, women and girls have lower participation levels than men and boys. This study adopted Millar and Doherty process model of capacity building to describe community sport clubs' response to local government policy on increasing the number of women and girls as players and leaders. Data regarding the need to build capacity to implement initiatives to recruit and retain women and girls were collected through an online survey targeting managers of sport clubs ( n = 20). Moderate levels of capacity were reported, however capacity building strategies did not align with clubs' specific capacity needs for initiatives to support women as leaders. Club readiness to build capacity to support women and girls as players was strong; nonetheless, club needs were somewhat addressed for these initiatives. Contributions to capacity building theory and implications for the clubs are presented.